Intellectual capital disclosure and profitability on Company value in Banking - Shofiyatul Innayah; Lia Uzliawati2; Agus Sholikhan Yulianto (Enrichment : Journal of Management, 2023)
Company Value consider by investors to make investment decisions. Companies that have high company value will affect investor confidence to invest in a company. Based on the phenomenon and agency theory, company value is influenced by Intellectual Capital Disclosure and Profitability. Intellectual capital is an intangible asset owned by a company that can have added value to company value. This study aims to examine the effect of Intellectual Capital Disclosure on Company value. The sample used in this study is the banking annual report listed on the IDX for 2017-2021. Multiple Regression is used as an analytical tool in this study. The results of the study show that intellectual capital disclosure has a significant negative effect on company value. Meanwhile, Profitability has a significant positive effect on company value. Profitability is a one mind factor that is considered by investors when making an investment.